2021
DOI: 10.1155/2021/5581319
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Nonperfusion Area on Ultra-Widefield Fluorescein Angiography and Nonflow Area on Optical Coherence Tomographic Angiography in Retinal Vein Occlusion

Abstract: Aims. To compare the relationship between the nonperfusion area (NPA) on ultra-widefield fluorescein angiography (UWFFA) and the nonflow area (NFA) on optical coherence tomographic angiography (OCTA) in retinal vein occlusion (RVO). Methods. Cross-sectional study. 46 eyes of 46 RVO patients who underwent UWFFA and OCTA. NPA and ischemic index (ISI) were quantified on UWWFA. NFA, vessel density (VD) of the superficial capillary plexus (SCP), the deep capillary plexus (DCP), and the size foveal avascular zone (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Indeed, previous studies' results only considered the area that we identified as complete ischemia. [3][4][5]11 Our data reveal that ISI does not correlate with FAZ and BCVA in BRVO eyes. While these association are wellestablished in CRVO, their existence is debated in BRVO.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Indeed, previous studies' results only considered the area that we identified as complete ischemia. [3][4][5]11 Our data reveal that ISI does not correlate with FAZ and BCVA in BRVO eyes. While these association are wellestablished in CRVO, their existence is debated in BRVO.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, there was no direct relationship between FAZ area and ISI, although a cut-off was found to identify patients with larger FAZ. 5,7 In terms of the effect of ISI on CMT, our data suggest that, in contrast to complete ischemia, only partial ischemia correlates with an increased CMT in BRVO eyes. However, in our study we could not find an association between the amount of pCNP and the response to anti-VEGF treatment in terms of CMT reduction.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There are some previous studies that have reported that the presence of the nonperfusion areas on UWFA is correlated with widefield OCTA. 7,8 However, our study is the first report to demonstrate that the peripheral nonperfusion area and retinal neovascularization could be identified with UWFA and widefield OCTA in a patient with Eales disease.…”
Section: Discussionmentioning
confidence: 58%
“…There are some previous studies that have reported that the presence of the nonperfusion areas on UWFA is correlated with widefield OCTA. 7,8 However, our study is the first report to demonstrate that the peripheral nonperfusion area and retinal neovascularization could be identified with UWFA and widefield OCTA in a patient with Eales disease. The differential diagnosis of Eales disease requires the exclusion of vascular occlusive diseases such as diabetic retinopathy, retinal vein occlusion, sarcoidosis, Behçet disease, Coats disease, familial exudative vitreoretinopathy, AIDS, tuberculosis, syphilis, and sickle cell disease.…”
Section: Discussionmentioning
confidence: 59%